Data analysis on herbal treatment for early-stage chronic kidney disease patients with proteinuria in Singapore Thong Chai Medical Institution - Lim, Rachel Qin Rui (Nanyang Technological University, 2022)
Objective. To identify patient characteristics and core herbs from prescriptions of early-stage chronic kidney disease (CKD) G1-G2 patients with proteinuria in Singapore Thong Chai Medical Institution (STCMI). Methods. Data of early-stage CKD patients with proteinuria from 1 January 2016 to 30 April 2022 were obtained from STCMI electronic medical record system. Baseline characteristics analysis was performed using R V4.2.0. Chinese herbal medicine (CHM) was analysed using Gu Jin Yi An Yun Platform V2.3.5 for herbal frequency and properties, association analysis, and core prescription network analysis. Results. 2890 herbal prescriptions from 111 CKD early-stage patients were analyzed. There was approximately 1:1 ratio of males and females. All patients were of Chinese ethnicity and the mean age was 67.3 ± 12.4. Core herbs identified were Poria (Fuling), Radix Astragali (Huangqi), Rhizoma Dioscoreae (Shanyao), Rhizoma Atractylodis Macrocephalae (Baizhu), Cordyceps Sobolifera (Jinchanhua), Pericarpium Citri Reticulatae (Chenpi), Radix Glycyrrhizae (Gancao), Codonopsis Radix (Dangshen), Cortex Eucommiae (Duzhong). Poria was the most frequently prescribed herb among a total of 320 herbs. Conclusions. This study has provided insights on the common herbs which are effective in the treatment of early-stage CKD patients with proteinuria.